(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
This article aims at considering the world cinema “perspective” in contemporary film studies as an approach that adopts a cartographical rhetoric and a worldist aesthetics. This reveals a nostalgia for the geographical discourse, which has many implications and can be even considered reactionary. Indeed, being the effect of a sort of osmosis between “cartographic cinema” and “cartography of cinema,” world cinema promotes a worldview that is allegorical of the old modernist cinematic mission of making the whole world visible. By reinserting geography in contemporary film studies and in the filmic texts today, it is compensative of new anxieties about film referentiality and the difficult mappability of informal film distribution. On a broader level, a symptomatic reading of world cinema shows how its geographical/ geopolitical gaze tries to overcome a crisis of authority and of representation, and the “crisis of the cartographic reason.”